Rediscovered syntypes of Procrangonyx japonicus, with nomenclatural consideration of some crangonyctoidean subterranean amphipods (Crustacea: Amphipoda: Allocrangonyctidae, Niphargidae, Pseudocrangonyctidae) - Nakano, Takafumi; Tomikawa, Ko; Grygier, Mark J. (Zootaxa, 2018)
Two missing syntypes of the Japanese subterranean amphipod Procrangonyx japonicus (Uéno, 1930), the type species of Procrangonyx Schellenberg, 1934, were rediscovered in the collections of the Kyoto University Museum. The morphology of uropod 3, which has been considered the principal diagnostic character of the genus, is redescribed on the basis of one of the syntypes, and the nomenclatural history of the generic names Procrangonyx and Eocrangonyx Schellenberg, 1937 (corrected from 1936) for some Far-Eastern subterranean amphipod species is reviewed. Owing to confusion between the terms “type fixation” and “type designation”—the latter being just one means of accomplishing the former—the view that Procrangonyx is unavailable and invalid has prevailed in recent literature. Procrangonyx was indeed proposed after 1930 with no type species “designation”, but under Articles 67.2.1 and 68.3 of the International Code of Zoological Nomenclature, Eucrangonyx japonicus Uéno, 1930 was “fixed” as its type species by monotypy in the original publication. Since a diagnosis of the genus was also provided in the same work, Procrangonyx is available under Article 13.3 of the Code. However, because endopodal segmentation of uropod 3 proves to be variable in P. japonicus, doubt is thrown on the taxonomic distinctness of Procrangonyx vis à vis Pseudocrangonyx Akatsuka & Komai, 1922. Additionally, the publication dates of Allocrangonyx Schellenberg, 1937 and Niphargus foreli speziae Schellenberg, 1937 are corrected from 1936.